2016
DOI: 10.1002/cbdv.201600136
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Antimicrobial Activity of the Essential Oil from Aerial Parts and Roots of Eryngium barrelieri Boiss. and Eryngium glomeratum Lam. from Tunisia

Abstract: The study of chemical composition and biological activity of unexplored essential oils may open new perspectives on their potential use in facing major health concerns such as drug-resistant infections. The present study investigates the chemical composition and antimicrobial effects of previously unstudied essential oils obtained from genus Eryngium: Eryngium glomeratum Lam. and Eryngium barrelieri Boiss. The chemical compositions of the essential oils from aerial parts and roots of both species were studied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 55 publications
0
15
0
1
Order By: Relevance
“…Eryngium is the largest genus in Apiaceae and is found on every continent except Antarctica. Several Eryngium species are used in various traditional medicine practices to treat conditions including hypertension, gastrointestinal distress, diarrhea, burns and fevers (Landoulsi et al, 2016). Five Mediterranean Eryngium species exhibited antibacterial activity including E. amethystinum L., E. campestre L., E. glomeratum Lam., E. palmatum Pančić & Vis.…”
Section: Apiaceaementioning
confidence: 99%
“…Eryngium is the largest genus in Apiaceae and is found on every continent except Antarctica. Several Eryngium species are used in various traditional medicine practices to treat conditions including hypertension, gastrointestinal distress, diarrhea, burns and fevers (Landoulsi et al, 2016). Five Mediterranean Eryngium species exhibited antibacterial activity including E. amethystinum L., E. campestre L., E. glomeratum Lam., E. palmatum Pančić & Vis.…”
Section: Apiaceaementioning
confidence: 99%
“…Küpeli et al [6] have also demonstrated that the aqueous and ethanol extract from the roots of eight Eryngium species possess anti-inflammatory and antinociceptive properties. Recently, Landoulsi et al [7] reported that the essential oil extracted from leaves and roots of Eryngium barrelieri and Eryngium glomeratum possessed antimicrobial activity. Numerous studies on phytochemical characterization of various species had been carried out.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies on phytochemical characterization of various species had been carried out. Triterpenoids, coumarins, acetylenes, essential oil, flavonoids, and steroids were identified as the main constituents [8,7].…”
Section: Introductionmentioning
confidence: 99%
“…The essential oils of 36 Eryngium species have already been studied and the sample oils can be divided into two main chemical compositions according to their main components. The first group is characterized by oxygenated compounds including sesquiterpenes such as γ ‐cadinen‐15‐al, spathulenol, sesquicineole, α ‐bisabolol, and cis ‐chrysanthenyl acetate, as well as nonterpenic compounds such as trimethylbenzaldehyde, ( E )‐2‐dodecenal, linear acids, and polyacetylenes . The second group includes sample oils with terpenic hydrocarbon compounds such as germacrene D, bicyclogermacrene, γ ‐muurolene, and trans ‐caryophyllene …”
Section: Introductionmentioning
confidence: 99%